Fabrication and Characterization of Carbonate Apatite-Bovine Gelatin Scaffolds for Endodontic Regeneration: A Lyophilization-Based Approach - Widyasari, Ratih; Cahyanto, Arief; Widyaputra, Sunardhi; Rachman, Arif (European Journal of Dentistry, 2025)
The challenge of endodontic regeneration requires scaffold that can facilitate dentin and pulp regeneration by providing structural support and promoting initial cell adherence to regenerate new tissue. This study explores characterization of a novel carbonate apatite-bovine gelatin (CA-BG) scaffold for endodontic regeneration that was fabricated using a lyophilization technique. CA, recognized for its biocompatibility and osteoconductive capabilities as a scaffold, was expected to provide structural support in complex biological environments such as pulp tissues. BG, a natural polymer with cell attachment substrates, was incorporated into the scaffold to enhance bioactivity, promoting cell attachment, proliferation, and differentiation.Scaffolds were fabricated with varying liquid-to-powder (L/P) ratios (0.5, 0.8, and 1) using freeze drying, and then their chemical and structural properties were evaluated using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM).FTIR analysis confirmed the presence of carbonate and phosphate groups, with slight peak shifts indicating CA-BG interaction. XRD analysis showed crystallinity differences, which were affected by the liquid ratio in each group. SEM results demonstrated that the L/P 1 scaffold exhibited surface roughness, which is expected to represent BG incorporation to CA. The L/P 1 scaffold was identified as the optimal candidate, balancing bioactivity and structural properties, to be able to promote dentin and pulp tissue regeneration.The findings contribute significantly to developing biocompatible, bioactive scaffolds for endodontic regeneration and broader tissue engineering applications, offering insights to achieve a balance between a scaffold structure and its biological functionality.
Keywords: bioactivity; bovine gelatin; carbonate apatite; crystallinity; endodontic regeneration; lyophilization; scaffold